Free Radical Medicine and Biology - Das, Kusal; Das, Swastika; Shivanagouda Biradar, Mallanagouda; Bobbarala, Varaprasad; Subba Tata, S. (Physiology, 2020)
Although free radicals perform some useful immune functions, they can also damage healthy cells through a process called oxidation. Antioxidants reduce the effect of free radicals by binding together with these harmful molecules, decreasing their destructive power. This book highlights various issues of free radical biology from the perspective of antioxidant defense mechanisms. It also provides useful information on gene modulation, radiation-generated reactive oxygen species-induced apoptosis in cancer, and environmental aspects associated with free radicals' exposure on living systems.